PENGARUH PENDEKATAN AESOPâS BERBANTUAN GUIDANCE WORKSHEET TERHADAP HASIL BELAJAR SISWA - Pahlevi, Mirza; -, Sudarmin; Prasetya, Agung Tri (Jurusan Kimia, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Semarang, 2013)
Learning activity will be fun and optimal when applied using an appropriate learningÂ media. One approach that can be used by teachers in teaching is the Aesops approach withÂ media assisted of Guidance Worksheet. This study aimed to determine whether the use of theÂ Aesops approach with media assisted of Guidance Worksheet have significant effect onÂ student learning outcomes in subject of hydrocarbons and wether it have Â effectiveness after itÂ applied on an high school student in Semarang. This study uses a real experiment design. TheÂ sampling technique used is cluster random sampling, one class was as an experimental classÂ using the Aesops approach with media assisted of Guidance Worksheet while one class was asÂ a control class using conventional methods. The intake of data research were obtained throughÂ the method of documentation, testing, observation and questionnaires. The average grade ofÂ post test in experimental class is 86.80 while in control class is 80.64. Hypothesis testingÂ obtained tÂ countÂ (4,858) > tÂ tableÂ (1,99), which means that an average grade of cognitive learningÂ outcomes in experiment class was better than the control class. It can be concluded that theÂ Aesops approach with media assisted of Guidance Worksheet had an effect on chemistryÂ learning outcomes of hydrocarbon subject and it increase the effectiveness of student learning.